Physicochemical Fingerprinting and Pollution Indicators of Hemodialysis Wastewater in a Developing Mediterranean Region - Malak A. D. Lajerd; Basmah A. Aldeeb; Wafa A. Aldeeb; Adel A. S. Banana (African Journal of Advanced Pure and Applied Sciences, 2026)
Wastewater generated from dialysis centers represents a significant environmental concern due to its complex physicochemical composition. These properties may alter environmental conditions and pose potential risks to ecosystem stability and public health. This study aimed to evaluate the physicochemical characteristics of blood dialysis waste and water rejected from the treatment units from dialysis centers in Riqdalin and Al-Jamil hospitals. Samples were collected periodically from the discharge points of both centers over a period of four months, from August to November 2025, and tested in accordance with standard methods of wastewater analysis. The physicochemical investigation focused on the extent of temperature (T), potential hydrogen (PH), electrical conductivity (EC), total dissolved solids (TDS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), dissolved oxygen (DO), nitrates (NO₃⁻), nitrites (NO2-), total nitrogen, total organic carbon (TOC), total phosphorus, and Oil & Grease. During an evaluation of effluent physicochemical properties of wastewater analysis, the effluents analyzed showed non-compliant with the WHO and Libyan standard specifications. The findings indicate an urgent need to develop specialized treatment strategies for this waste prior to final discharge to mitigate its environmental and health impacts.